Images of the tropics: Environment and visual culture in colonial Indonesia - Protschky, Susie (Verhandelingen van het Koninklijk Instituut voor Taal-, Land- en Volkenkunde, 2011)
Images of the Tropics critically examines Dutch colonial culture in the Netherlands Indies through the prism of landscape art. Susie Protschky contends that visual representations of nature and landscape were core elements of how Europeans understood the tropics, justified their territorial claims in the region, and understood their place both in imperial Europe and in colonized Asia during the nineteenth and early twentieth centuries. Her book thus makes a significant contribution to studies of empire, art and environment, as well as to histories of Indonesia and Europe.